When Sustainability Meets Emissions: Factors Shaping ESG Performance in Indonesian Manufacturing Firms - Hery Haryanto; Muhammad Akbar Nanditama; Yandi Suprapto (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2026)
Main Purpose - This research investigates the impact of R&D spending, eco-friendly innovation, and Corporate Social Responsibility on Environmental, Social, and Governance performance. It additionally examines the moderating effect of carbon emissions in these connections among Indonesian manufacturing firms. Method - A quantitative explanatory strategy was utilized, employing panel data from 23 manufacturing companies listed on the Indonesia Stock Exchange (2019–2023), chosen through purposive sampling. Panel regression and moderated regression analysis in STATA were utilized to analyze secondary data from annual reports, sustainability reports, and ESG rating databases. Main Findings - To achieve sustainable development, Indonesian policymakers and industry executives need to promote cohesive corporate strategies. Policies must encourage companies to integrate environmental innovation (R&D, green technology) and emissions management with fundamental ESG frameworks to improve long-term competitiveness and sustainable development. Theory and Practical Implications - To achieve sustainable development, Indonesia's policymakers and industry leaders need to promote cohesive corporate strategies. Policies ought to encourage companies to integrate environmental innovation R&D, green technology, and emission management with essential ESG frameworks to boost long-term competitiveness and sustainable development. Novelty - This research adds to the knowledge by treating ESG performance as the dependent variable and incorporating carbon emissions as a new moderating factor, offering vital empirical insights from a less studied emerging market scenario.